Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1227/01.neu.0000489705.76089.c2
|View full text |Cite
|
Sign up to set email alerts
|

135 A Comparison of Outcomes Between Deep Brain Stimulation Under General Anesthesia Versus Conscious Sedation With Awake Evaluation

Abstract: International audienceINTRODUCTION: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) for the management of motor symptoms of Parkinson disease (PD) is typically performed under conscious sedation with awake evaluation during intraoperative physiologic testing. However, developments in surgical techniques now allow for subjects to be asleep during the procedure using general anesthesia. Previously reported long-term outcomes of subjects who underwent STN-DBS under general anesthesia demonstrated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A recent multicenter European trial of 40 PD patients undergoing bilateral STN stimulation also found no significant difference in motor function outcomes of patients undergoing DBS with general anesthesia and those of patients who underwent DBS under conscious sedation. 1 Additionally, in a study of 14 asleep patients and 68 awake patients undergoing bilateral STN stimulation, Nakajima and colleagues 18 found no difference in the percentage improvement in postoperative OFF/ON UPDRS-III scores compared with preoperative off-medication scores between awake (50.8%) and asleep (52.8%) groups (p = 0.96). For patients who underwent the asleep DBS technique, the percentage of motor score improvement was similar to that previously reported in awake DBS studies (GPi, 28%-33%; STN, 25%-52%) 8,19 and in asleep DBS series (GPi and STN, 40%-52%).…”
Section: Primary Outcomementioning
confidence: 97%
“…A recent multicenter European trial of 40 PD patients undergoing bilateral STN stimulation also found no significant difference in motor function outcomes of patients undergoing DBS with general anesthesia and those of patients who underwent DBS under conscious sedation. 1 Additionally, in a study of 14 asleep patients and 68 awake patients undergoing bilateral STN stimulation, Nakajima and colleagues 18 found no difference in the percentage improvement in postoperative OFF/ON UPDRS-III scores compared with preoperative off-medication scores between awake (50.8%) and asleep (52.8%) groups (p = 0.96). For patients who underwent the asleep DBS technique, the percentage of motor score improvement was similar to that previously reported in awake DBS studies (GPi, 28%-33%; STN, 25%-52%) 8,19 and in asleep DBS series (GPi and STN, 40%-52%).…”
Section: Primary Outcomementioning
confidence: 97%
“…From the surgical point of view, eligible candidates for the DBS procedure should be in a satisfactory general and cognitive condition. Even though there is no difference in motor function outcomes for performing the surgery awake or under general anesthesia ( 183 ), most of the surgeries are realized with patients awake in order to perform intraoperative neurological tasks. In PD patients, concomitant disorders concerning blood clotting abnormalities, cardiovascular diseases and immune deficiencies should be evaluated.…”
Section: Clinical Aspects Of Dbs Surgerymentioning
confidence: 99%
“…Recent advances in intraoperative imaging have allowed targeting based on anatomy alone under general anesthesia without awake physiological and behavioral testing. Early experience with relatively small samples shows similar efficacy versus traditional awake surgery, although efficacy, adverse events, and postoperative side effects have not been compared in a prospective, randomized fashion [10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%